2021
DOI: 10.1073/pnas.2021965118
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-dependent heterosis in maize

Abstract: Hybrids account for nearly all commercially planted varieties of maize and many other crop plants because crosses between inbred lines of these species produce first-generation [F1] offspring that greatly outperform their parents. The mechanisms underlying this phenomenon, called heterosis or hybrid vigor, are not well understood despite over a century of intensive research. The leading hypotheses—which focus on quantitative genetic mechanisms (dominance, overdominance, and epistasis) and molecular mechanisms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 45 publications
(48 reference statements)
1
27
0
Order By: Relevance
“…In spite of F 2 hybrid breakdown, we detected no postzygotic isolation in ponds because of counteracting heterosis. We detected heterosis in aquarium-raised limnetic F 1 hybrids but not in benthic F 1 hybrids, which is consistent with previous findings that features of the environment can underlie heterosis [64]. F 1 heterosis (and F 2 breakdown) is regularly observed in plants [65][66][67][68], but is not as common in outbred wild animal species.…”
Section: Discussionsupporting
confidence: 91%
“…In spite of F 2 hybrid breakdown, we detected no postzygotic isolation in ponds because of counteracting heterosis. We detected heterosis in aquarium-raised limnetic F 1 hybrids but not in benthic F 1 hybrids, which is consistent with previous findings that features of the environment can underlie heterosis [64]. F 1 heterosis (and F 2 breakdown) is regularly observed in plants [65][66][67][68], but is not as common in outbred wild animal species.…”
Section: Discussionsupporting
confidence: 91%
“…How common, then, is this pattern? While there are many excellent examples of environment‐dependent heterosis, they rarely match the pattern described exactly—either because F1 fitness is intermediate in one of the environments (e.g., Crespel et al., 2012 , 2012 ; Martins et al., 2019 ; Munaro et al., 2011 ; Vetukhiv & Beardmore, 1959 ; Walter et al., 2020 ; Wu & Campbell, 2006 ; Wang et al., 2022 ), or because F1 fitness was not available for the individual cross directions (e.g., Benyi & Gall, 1981 ; Dittrich‐Reed, 2013 ; Domgínguez & Albornoz, 1987 ; Harrison, 1962 ; Maynard Smith, 1956 ; Stojanova et al., 2021 ; Wagner et al., 2021 ). As such we have found only two possible examples of the complete pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the soil microbes in heterosis has largely been ignored. A first study by Wagner et al (2021) has shown that the heterosis of the root biomass and other traits in maize depends to a great extent on the belowground microbial environmental, although the intrinsic profile of the natural soil can drive the responses in different ways. All this underlines the importance of microbiologically defining the soil that acts as a control group in each experiment that involves microbial effectors.…”
Section: Discussionmentioning
confidence: 99%